Effektivpreise, Lebenskosten und Kaufkraft des Geldes im Niedrigzinsumfeld - Karl-Heinz Tödter; Gerhard Ziebarth (Research On Money in the Economy (ROME), 2018)
– For the purposes of private consumption present and future goods are constantly evaluated and traded. A reliable und comprehensive measure of the general purchasing power of money and its changes over time should take due account of this basic fact. In contrast to conventional statistical consumer price indexes, an economic cost of life index is of intertemporal nature by construction as it incorporates the effective consumer prices over the planning horizon of private households. Any standard of price stability that suppresses this interrelationship tends to be biased and bears the risk of asymmetric monetary policy. Effective prices are present value prices for future consumption, include goods prices as well as interest rates (and asset price changes, respectively), are based on consumer utility and welfare theory, and are forming the central building blocks for the model class of economic cost of life indices. Given the preference based approach, effective prices are money valued marginal utilities of the final unit consumed. Effective inflation rates derived from effective prices are intertemporal marginal rates of substitution. The present paper develops an intertemporal cost of life index based on the concept of effective prices and presents empirical time series and cohort-specific scenario results for Germany.
Keywords: D15; E31; E21; E58; I3; 330; Purchasing power of money; monetary policy; interest rates; present value prices; asset prices; effective inflation; cost of life index